2012
DOI: 10.1177/070674371205701107
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hospital Length of Stay for Geriatric Patients with Mood Disorders

Abstract: Objective: To determine predictors of hospital length of stay (LOS) for adult and geriatric patients with mood disorders admitted to inpatient psychiatric beds.Method: Admission and discharge data from a large urban mental health centre, from 2005 to 2010 inclusive, were retrospectively analyzed. Using the Resident Assessment Instrument-Mental Health, an assessment that is used to collect demographic and clinical information within 72 hours of hospital admission, 199 geriatric mood disorder admissions were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
7
2
Order By: Relevance
“…The mean LOHS of late-onset depressive patients in our study (83.9 1 55.6 days) is longer than that in the study by Ismail et al in Canada (61.0 1 70.6 days). 2 However, it is noteworthy that their study did not differentiate between late-onset and early-onset depression.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The mean LOHS of late-onset depressive patients in our study (83.9 1 55.6 days) is longer than that in the study by Ismail et al in Canada (61.0 1 70.6 days). 2 However, it is noteworthy that their study did not differentiate between late-onset and early-onset depression.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Ismail et al reported that living alone, the number of recent psychiatric admissions, and involuntary admission predict longer LOHS in elderly patients with depression in a Canadian population. 2 However, late-onset depression is known to be associated with a higher rate of comorbidity, ageing-related vascular changes, 3 higher severity, 4 a greater incidence of completed suicide, 5 and poorer outcomes than early-onset depression. 6 Thus, the clinical differentiation between late-onset and early-onset depression is necessary in order to investigate the predictors of longer LOHS among elderly depression patients.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been noted to prolong length of hospital stay is nonobstetric [32,33] and obstetric populations [34]; however, it is unclear whether hospitalized women with high obstetric risk are more likely to experience depression [2,12]. Thus, there is a need for studies that examine change in depression symptoms over the course of hospitalization [13].…”
Section: Discussionmentioning
confidence: 99%
“…Depression has been noted to prolong length of hospital stay is non-obstetric [32, 33] and obstetric populations [34], however it is unclear whether hospitalized women with high obstetric risk are more likely to experience depression [2, 12]. Thus, there is a need for studies that examine change in depression symptoms over the course of hospitalization [13].…”
Section: Discussionmentioning
confidence: 99%